2022
DOI: 10.1371/journal.ppat.1010569
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal kinetics of RBD+ antibodies in COVID-19 recovered patients over 14 months

Abstract: We describe the longitudinal kinetics of the serological response in COVID-19 recovered patients over a period of 14 months. The antibody kinetics in a cohort of 192 recovered patients, including 66 patients for whom follow-up serum samples were obtained at two to four clinic visits, revealed that RBD-specific antibodies decayed over the 14 months following the onset of symptoms. The decay rate was associated with the robustness of the response in that antibody levels that were initially highly elevated after … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(42 reference statements)
1
5
1
1
Order By: Relevance
“…This study extends our previous work showing that anti-SARS-CoV-2 spike antibodies remain detectable after 22 months past probable infection as measured with the Roche anti-S immunoassay (Perez-Saez et al, 2021). Our kinetic modeling results support previous findings indicating that antibody boost is strongest and longest lasting in vaccinees with a history of infection (Dimeglio et al, 2022a;Eyran et al, 2022;Luo et al, 2021). In contrast with previous findings, we found no significant difference in antibody boosting between age groups and slower decay rates in adults 65 years and older (Gallais et al, 2021;Vanshylla et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study extends our previous work showing that anti-SARS-CoV-2 spike antibodies remain detectable after 22 months past probable infection as measured with the Roche anti-S immunoassay (Perez-Saez et al, 2021). Our kinetic modeling results support previous findings indicating that antibody boost is strongest and longest lasting in vaccinees with a history of infection (Dimeglio et al, 2022a;Eyran et al, 2022;Luo et al, 2021). In contrast with previous findings, we found no significant difference in antibody boosting between age groups and slower decay rates in adults 65 years and older (Gallais et al, 2021;Vanshylla et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The evaluation of binding antibody levels as correlates or protection is challenged by the constant evolution of the anti-SARS-CoV-2 immune landscape through vaccination and successive epidemic waves driven by different virus variants. Longitudinal antibody studies up to 14 months follow-up have shown that antibody levels change with time since infection and/or vaccination across individuals, and depending on the immuno-assays used for detection (Eyran et al, 2022;Gallais et al, 2021;Peluso et al, 2021;Perez-Saez et al, 2021). Characterization of long-term antibody kinetics provides an opportunity for leveraging serological cohort studies to complement vaccine trials in evaluating binding antibody levels as correlate of protection against future infections.…”
Section: Introductionmentioning
confidence: 99%
“…5 Facultat de Medicina, Universitat de Vic-Universitat Central de Catalunya (UVIC-UCC), Vic, Spain. 6 Biomolecular Screening and Protein Technologies Unit, Centre for Genomic Regulation (CRG), The Barcelona Institute of Science and Technology, Barcelona, Spain. 7 Centre d' Atenció Primària (CAP) Sant Joan de Vilatorrada.…”
Section: Supplementary Informationunclassified
“…We have previously shown that 90% of those infected with SARS-CoV-2 remain seropositive 1 year after discharge [1,2]. To our knowledge, the duration of antibody responses following natural infection has not been assessed beyond 13-20 months to date [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Initial immunity after infection was assumed perfect, with all infected people transiting to an immune state upon recovery from infection. The duration of immune protection varied according to vaccination status, as well as prior infection status among vaccinated individuals (11, 18, 19). Anti-spike antibody titres have been demonstrated to be a consistent correlate of protection against SARS-CoV-2 infection (20).…”
Section: Methodsmentioning
confidence: 99%